2008
DOI: 10.1590/s0100-29452008000100036
|View full text |Cite
|
Sign up to set email alerts
|

Divergência genética entre progênies de maracujazeiro- amarelo com base em características das plântulas

Abstract: O objetivo do presente trabalho foi avaliar a diversidade genética entre 24 populações de maracujazeiro-amarelo, discriminando os caracteres mais importantes na avaliação da divergência genética, com base em características das plântulas. Foram coletadas sementes de frutos obtidos a partir de polinização natural de vinte e quatro populações segregantes de meios-irmãos de maracujazeiro-amarelo. Utilizou-se delineamento experimental inteiramente casualizado, em vinte e quatro tratamentos (populações segregantes)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 4 publications
1
18
0
3
Order By: Relevance
“…When genetic diversity is studied using the canonical variables method, the main aim is to identify similar genotypes in twoor three-dimensional scatter plots, which makes it easier to simplify the interpretation of the results (NEGREIROS et al, 2008). In this paper, the analysis using the canonical variables method significantly represented all of the genetic diversity existing between the genotypes in a two-dimensional chart.…”
mentioning
confidence: 99%
“…When genetic diversity is studied using the canonical variables method, the main aim is to identify similar genotypes in twoor three-dimensional scatter plots, which makes it easier to simplify the interpretation of the results (NEGREIROS et al, 2008). In this paper, the analysis using the canonical variables method significantly represented all of the genetic diversity existing between the genotypes in a two-dimensional chart.…”
mentioning
confidence: 99%
“…The same did not occur in the studies of Negreiros et al (2008), which, working with genetic diversity among yellow passion fruit progenies based on seed characteristics, observed that the graphic dispersion by means of Canonic Variables presented behavior similar to the Tocher grouping.…”
Section: Resultsmentioning
confidence: 74%
“…bras., Brasília, v.52, n.8, p.607-614, ago. 2017 DOI: 10.1590/S0100-204X2017000800006 germination chamber (Brasil, 2009); first germination count, evaluated together with the germination test, for which normal seedlings were recorded at 14 days; accelerated aging, in which the seeds were placed on an aluminum screen, in a transparent plastic box, with 40 mL of water, where they remained for 48 hours, at 40ºC, in a germination chamber (Larré et al, 2007), before being subjected to the same methodology of the germination test, for which normal seedlings were recorded at 28 days (Brasil, 2009); first count of the accelerated aging test, for which the normal seedlings were counted at 14 days; seedling size, by using ten seedlings located at the top row of the paper roll at the end of the germination test (Negreiros et al, 2008); rootlet size, obtained from the measurement of the rootlets of ten seedlings located at the top row of the roll at the end of the germination test (Negreiros et al, 2008); and germination rate index, for which the number of normal seedlings was recorded every four days (Maguire, 1962). The canonical correlation was used to estimate the maximum correlation of the linear combinations (Cruz et al, 2012) between production traits (set 1: productivity, pulp mass, fruit mass, and number of fruits per plant), seed morphological traits (set 2: seed length/width ratio, seed thickness, and 1,000 seed weight), and seed physiological traits (set 3: germination potential, first germination count, first count of the accelerated aging test, accelerated aging, seedling size, rootlet size, and germination rate index).…”
Section: Methodsmentioning
confidence: 99%